Programa de estimulación en estrategias de aprendizaje en niños y niñas en edad preadolescente - Quiceno Jimenez, Diana Paola; Maldonado Cedano, Karent (Universidad Antonio Nariño, 2021)
The research project presents the general objective of designing a stimulation program in learning strategies called "PSICOLEARN" aimed at boys and girls from the San José educational institution in the city of Ibague, the program consists of 8 sessions, with an intensity of 1 weekly session and a duration of 2 hours per session. The sample was made up of 24 students (men and women) between the ages of 12 and 16; the paradigm with which the present investigation was approached is empirical analytical, the type of sampling was non-probabilistic, the approach used is quantitative, since the measurement instruments such as: Sociodemographic data sheet, ACRA (learning strategies) were applie) which is constituted by four scales, which are acquisition, coding, recovery and support. The present study is of a quasi-experimental type of (pre) test - (post) cross-section test, since it focuses on the study of variables and their development within a period of 2 months. The results obtained in this work show a significant increase in learning strategies where the attention and repetition processes showed a positive improvement in terms of reviewing aloud, mentally and repeatedly, considering that this scale requires more training for its use is reflected.